Designing Social Inquiry in Central Asia – A Case Study of Kyrgyzstan and Tajikistan - Kevlihan, Robert (Studies of Transition States and Societies, 2013)
Central Asia offers a potential smorgasbord for researchers engaged in comparative analysis. Common shared characteristics of these states have provided and continue to provide opportunities for advances in our understanding of political and social phenomena of global importance, including state building, democratisation, nationalism and economic development. However, in conducting comparative case study research in Central Asia, researchers should be aware of the strengths and weaknesses of different comparative approaches. This article reviews and critiques one approach to comparative analysis that has become increasingly dominant in social science research, particularly in the US. Comparing events in two Central Asian countries during 2005, a period of heightened risk of colour revolution, the article highlights both strengths and weaknesses of this increasingly dominant approach, arguing instead for a more inclusive and pragmatic approach to comparative analysis both in Central Asia and to case study comparisons more generally as the best way to advance our understanding of important social and political phenomena.